2017
DOI: 10.56278/tnl.v11i2.536
|View full text |Cite
|
Sign up to set email alerts
|

Why I Want to Teach: Exploring Factors Affecting Students' Career Choice to Become Teachers

Abstract: This is a qualitative study which explores different factors affecting the career decision-making of Grade 10 students leading to a choice of becoming a teacher. A total of 388 students participated in the study with 40 students from Metro Manila who conveyed they are pursuing teaching as a career. Data analysis involved coding and categorizing of responses with defining of emerging themes related to students' motivation to teach. It had two levels of data collection: survey questionnaire to gather student's p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…In spite of the given state, graduating students from secondary schools enter college without a clear idea and solid decision on what degree program or career to pursue (Ramirez & Dizon, 2014). Mangaoil, Rungduin, Abulencia, and Reyes (2017) pointed out that incoming college students experienced indecision concerning career decision-making, which their parents have influenced their career choice. Many students don't have enough capacity and consciousness to process and apply information from different perspectives, and have difficulty in contextualizing this knowledge for the realization of their profession (Aguado, Laguador, & Deligero, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the given state, graduating students from secondary schools enter college without a clear idea and solid decision on what degree program or career to pursue (Ramirez & Dizon, 2014). Mangaoil, Rungduin, Abulencia, and Reyes (2017) pointed out that incoming college students experienced indecision concerning career decision-making, which their parents have influenced their career choice. Many students don't have enough capacity and consciousness to process and apply information from different perspectives, and have difficulty in contextualizing this knowledge for the realization of their profession (Aguado, Laguador, & Deligero, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Oruc (2011) guru bukan hanya tentang mengajar dan membimbing namun lebih dari itu mereka juga dituntut untuk mendidik karakter pribadi dari peserta didik. Penelitian dari Mangaoil (2017) menyebutkan bahwa dalam pendidikan tinggi guru sebagai tenaga pengajar turut berperan dan berkontribusi dalam menentukan keberhasilan belajar peserta didik.…”
unclassified
“…Further, interview respondents reported that they had informal teaching experiences or had experienced teacher-like activities; and, the choice of teaching was driven by the joy they found in such experiences. These findings suggest that many students are highly motivated and attracted to teaching, contrary to the claim that students choose teaching because they have no other choice (Mangaoil et al, 2017). In light of Wigfield and Eccles's (2000) expectancy-value model, individuals select an occupational choice that is in line with their hierarchy of expectancy for success (i.e.…”
Section: Motivational Factors Influenencing Teaching As a Career Choicementioning
confidence: 87%